Declining growth of deciduous shrubs in the warming climate of continental western Greenland. (7th November 2017) - Gamm, Cassandra M.; Sullivan, Patrick F.; Buchwal, Agata; Dial, Roman J.; Young, Amanda B.; Watts, David A.; Cahoon, Sean M. P.; Welker, Jeffrey M.; Post, Eric
Abstract: Observational and experimental studies have generally shown that warming is associated with greater growth and abundance of deciduous shrubs in arctic ecosystems. It is uncertain, however, if this trend will persist in the future. Our study examined growth responses of deciduous shrubs to climate change over the late 20th and early 21st centuries near Kangerlussuaq in western Greenland. We combined shrub dendrochronology, stable isotope analysis and weekly measurements of leaf gas exchange to examine the drivers of secondary growth in two widespread and dominant deciduous shrub species: Salix glauca and Betula nana . Betula showed a dramatic growth decline beginning in the early 1990s, when correlations between growing season air temperature and growth shifted from neutral to strongly negative. Salix also showed a growth decline, but it began slightly later and was more pronounced among older stems. May–August mean air temperature of c . 7°C appeared to be an important threshold. Carbon isotope discrimination (∆ 13 C) in α‐cellulose of Salix growth rings declined strongly during the period of reduced growth, suggesting drought‐induced stomatal closure as a possible cause. Leaf gas exchange of Salix was also highly sensitive to seasonal variation in moisture availability. Betula growth declined more dramatically than Salix, but leaf gas exchange was less sensitive to moisture availability and there was less evidence of a ∆ 13 C trend. We hypothesize that the dramatic Betula growth decline might reflect the combined effects of increasing moisture limitation, repeated defoliation during recent moth outbreaks and greater browsing by a growing muskoxen population. Synthesis . Our findings contrast with widespread observations of increasing shrub growth in the Arctic and instead point to a potential decline in the flux of carbon into a pool with a long mean residence time (wood). While our study area is warmer and drier than much of the Arctic, our results may serve as an early indicator of potential effects of rising temperature in other arctic ecosystems. Abstract : We combined physiological measurements with shrub dendrochronology to examine drivers of secondary growth in two dominant deciduous shrubs. We found growth declines in both species that were at least partially associated with moisture limitation. While our study area is relatively warm and dry, our results may serve as an early warning of potential climate change effects in other arctic ecosystems.